Factors Associated With Nonadherence in an Emergency Department-based Multicenter Randomized Clinical Trial of a Probiotic in Children With Acute Gastroenteritis. Issue 1 (January 2021) - Schnadower, David; Roskind, Cindy G.; VanBuren, John M.; Powell, Elizabeth C.; Norris, Jesse G.; Tarr, Phillip I.; Sapien, Robert E.; O'Connell, Karen J.; Chun, Thomas H.; Rogers, Alexander J.; Bhatt, Seema R.; Mahajan, Prashant; et al.
Abstract : ABSTRACT: Nonadherence in clinical trials affects safety and efficacy determinations. Predictors of nonadherence in pediatric acute illness trials are unknown. We sought to examine predictors of nonadherence in a multicenter randomized trial of 971 children with acute gastroenteritis receiving a 5-day oral course of Lactobacillus rhamnosus GG or placebo. Adherence, defined as consuming all doses of the product, was reported by the parents and recorded during daily follow-up contacts. Of 943 patients with follow-up data, 766 (81.2%) were adherent. On multivariate analysis, older age (OR 1.19; 95% CI: 1.00–1.43), increased vomiting duration (OR 1.23; 95% CI: 1.05–1.45), higher dehydration score (OR 1.23, 95% CI: 1.07–1.42), and hospitalization following ED discharge (OR 4.16, 95% CI: 1.21--14.30) were factors associated with nonadherence; however, those with highest severity scores were more likely to adhere (OR 0.87, 95% CI: 0.80–0.95). These data may inform strategies and specific targets to maximize adherence in future pediatric trials. Abstract : Supplemental Digital Content is available in the text